Constitutional and genetic model of high coronary heart disease risk - O. I. Boeva; A. V. Yagoda; E. A. Koshcheeva (Кардиоваскулярная терапия и профилактика, 2007)
Aim. To study the complex somato-typological and psycho-typological features of coronary heart disease (CHD) patients, to assess prognostic value of these features, to evaluate the potential of genetic markers in persons with high CHD risk. Material and methods. In 215 patients with Functional Class I-IV stable angina, anthropometry parameters, phenotypical markers, dysembryogenesis stigmas, and psycho-typological personality structure were examined. The control group included 120 healthy persons. Results. In CHD patients, the following constitutional and genetic markers were combined: isteroid personal psycho-type, obesity, protruded ears, low hair borderline, blood group A (II), chin dimple, moderate joint hypermobility, moist cerumen, hair lines, and dark hair color. Linear function classification equation was developed, where Y parameter classified individuals with increased CHD risk. Conclusion. The complex of constitutional, psycho-typological and somato5typological features of CHD patients was used for creating high CHD risk identification model. In out-patient clinical practice, this model could facilitate primary CHD prevention measures in risk groups.